A retrospective review of adherence to dosing guildliness of amphotericin B for the treatment of cryptococgal meningitis at UTH - Zulu Phillimon (Lusaka, the university of Zambia, school of medicine, 2016)
It is worthy to note that, the past 50 years of therapeutics, amphotericin B has been the mainstay for treatment of cryptococcal meningitis. in an era of evidence based medicne, we remain uncertain regarding the appropriate dose of this drug for patients' treatment.
A dissertation subimtted in partial fulfilment for the award of bachelor of pharmacy degree at the university of Zambia.
Keywords: Meningitis